Use of amniotic fluid lactate concentration in prediction of dysfunctional labour at the University College Hospital, Ibadan. (2023)
Introduction: Dysfunctional labour is a common indication for instrumental vaginal delivery or cesarean section. Raised myometrial lactate level following prolonged uterine activities has been shown to cause inhibition of contractions (poor or uncoordinated) and lack of progress or dysfunctional labour. Therefore, determining the amniotic fluid lactate concentration (AFLC) in labour may be a potential biochemical marker for labour dystocia and a good predictor of labour outcome. Methodology: We recruited booked, consenting parturients in active phase of labour into a cross-sectional study between September 2014 and March 2015. Amniotic fluid samples were taken twice – at initial vaginal examination or during artificial rupture of membranes and at delivery while the AFLC was determined using a primed lactate meter. Results: The main outcome measure was the mean AFLC. Of the 113 parturients with mean age of 30.49 ± 4.37 years, the overall mean AFLC was 18.94 ± 4.84 mmol/L while 10 (8.8%) had dysfunctional labour. Mean AFLC for parturients who had vaginal delivery was 18.76 ± 4.90mmol/L and 17.42 ± 5.26 mmol/L at first and second samplings while for those who had cesarean deliveries, mean AFLCs were 20.80 ± 2.75 and 18.24 ± 3.59 at the two samplings respectively. The cut–off for AFLC that best discriminated between normal and dysfunctional labour was 19.80 mmol/L. Conclusion: High levels of AFLC may play a role in predicting dysfunctional labour among pregnant women in labour.